Convert FOL clauses to PROLOG

I am very new to PROLOG so it might be a very trivial question, but I absolutely have no idea how to solve it. There are 4 sentences I need to formulate into PROLOG code:

• All hounds howl at night.

• Anyone who has any cats will not have any mice.

• Light sleepers do not have anything which howls at night.

• John has either a cat or a hound.

I convert sentences to well-formed formula in first-order predicate calculus like that

- ∀x (HOUND(x) → HOWL(x))

- ∀x ∀y (HAVE(x,y) ∧ CAT (y) → ¬∃z (HAVE(x,z) ∧ MOUSE (z)))

- ∀x (Light_Sleeper(x) → ¬∃y (HAVE (x,y) ∧ HOWL(y)))

- ∃x (HAVE (John,x) ∧ (CAT(x) ∨ HOUND(x)))


Now I don't know how to write them in Prolog. Also, how can I make query on them?

• There are no trivial prolog questions, so don't despair! Commented Jan 1, 2019 at 13:36
• Why do you think you can convert arbitrary first-order formulas into Prolog? Commented Jan 1, 2019 at 13:43
• @DerekElkins If I can't convert the FOL into Prolog .. what would I do to convert the previous English sentences into Prololg? Commented Jan 1, 2019 at 15:04
• Again, why do you think that's something you can do? Commented Jan 1, 2019 at 22:29